(untitled) (SCIENCE TIME JOURNAL, 2024)
This paper examines the functional-semantic characteristics of descriptive nominal units in Uzbek and Russian. It explores the differences and similarities between nominal expressions in the two languages in terms of function and meaning. Uzbek and Russian often express descriptive units through adjectives, which serve essential roles in communication, reflecting cultural and semantic nuances. This topic is relevant in the fields of linguistics, translation studies, and cultural studies.